2007
DOI: 10.1080/17513750701450235
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity, persistence, and collapse in host–parasitoid systems with egg limitation

Abstract: There is an emerging consensus that parasitoids are limited by the number of eggs which they can lay as well as the amount of time they can search for their hosts. Since egg limitation tends to destabilize hostparasitoid dynamics, successful control of insect pests by parasitoids requires additional stabilizing mechanisms such as heterogeneity in the distribution of parasitoid attacks and host density-dependence. To better understand how egg limitation, search limitation, heterogeneity in parasitoid attacks, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Provided that F is continuous, and f is a compact map, Proposition 6.1 implies that there is a quasi-stationary distribution µ ε for X ε t with ε > 0. To understand the support of the weak* limit points µ of µ ε , we focus on a generalized Thompson model [Thompson (1924), Getz and Mills (1996), Schreiber (2006aSchreiber ( , 2007]. For this model, f (x 1 ) = exp(r(1 − x 1 /K)) is given by the Ricker equation where r > 0 is the intrinsic rate of growth of the host, and K > 0 is the host's carrying capacity.…”
Section: Metapopulation Dynamicsmentioning
confidence: 99%
“…Provided that F is continuous, and f is a compact map, Proposition 6.1 implies that there is a quasi-stationary distribution µ ε for X ε t with ε > 0. To understand the support of the weak* limit points µ of µ ε , we focus on a generalized Thompson model [Thompson (1924), Getz and Mills (1996), Schreiber (2006aSchreiber ( , 2007]. For this model, f (x 1 ) = exp(r(1 − x 1 /K)) is given by the Ricker equation where r > 0 is the intrinsic rate of growth of the host, and K > 0 is the host's carrying capacity.…”
Section: Metapopulation Dynamicsmentioning
confidence: 99%
“…Such a buffering mechanism may be adaptive in environments with variable host densities (Sevenster et al. ) and this as well as a low risk of starvation may result in greater host suppression (Getz and Mills ; Schreiber ).…”
Section: Discussionmentioning
confidence: 99%
“…They found 18% of the dissected individuals had an egg load of zero and, consequently, were extremely egg limited. Several theoretical studies have examined the combined effects of egg limitation and search limitation on host-parasitoid dynamics [6,10,26,30,27,28]. If one takes a broad view that egg limitation is a form of predator saturation, then it can be said that Rogers [26] was the first to consider egg limitation by translating Holling's type II functional response to a host encounter rate.…”
mentioning
confidence: 99%
“…Studying models without host self-regulation, Getz and Mills [6] found that stability of the host-parasitoid equilibrium requires parasitic attacks to be sufficiently aggregated and the intrinsic fitness of the parasitoid to exceed the intrinsic fitness of the host. Including host regulation, Schreiber found that parasitoids with aggregated attacks and sufficiently weak search limitation can suppress their hosts to extremely low densities and even drive them to extinction [27,28]. None of these studies, however, considered how egg limitation influences multiparasitoid-host interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation